Patterns of Nutrient Intake in Relation to Sarcopenia and Its Components - Bagheri, Amir; Hashemi, Rezvan; Heshmat, Ramin; Motlagh, Ahmadreza Dorosty; Esmaillzadeh, Ahmad (Frontiers in Nutrition, 2021)
Background: Despite the associations between individual nutrients and sarcopenia, we are aware of no information about the link between patterns of nutrient intake and odds of sarcopenia and its components. The present study aimed to examine the association between nutrient-based dietary patterns and sarcopenia and its components among Iranian adult population. Methods: In this population-based cross-sectional study, we enrolled 300 elderly adults (150 men and 150 women) aged ≥ 55 years by using cluster random sampling method. Dietary intakes of the study population were assessed using a validated food frequency questionnaire. Principal components analysis was conducted to derive nutrient patterns based on a daily intake of 33 nutrients. Muscle mass, muscle strength, and gait speed were measured according to standard methods. Sarcopenia and its components were defined based on The European Working Group on Sarcopenia. Results: Three major nutrient-based dietary patterns were identified: 1) “Pro-Vit pattern” that was high in pantothenic (B5), cobalamin (B12), calcium, protein, phosphor, riboflavin (B2), zinc, cholesterol, saturated-fat, folate, niacin (B3), selenium, vitamin D, vitamin K, and vitamin A; 2) “Anti-inflammatory” pattern which was rich in polyunsaturated fat, monounsaturated fat, copper, vitamin E, omega-3, magnesium, iron, pyridoxine (B6), sodium and caffeine; 3) “Carbo-vit” pattern which is characterized by high intakes of fructose, glucose, dietary fiber, biotin, potassium, thiamin (B1), vitamin C, and chromium. After adjusting for confounders, subjects in the top tertile of the anti-inflammatory pattern had lower odds of sarcopenia (OR 0.25; 95 % CI 0.10-0.63) and low muscle strength (OR: 0.46; 95% CI: 0.22-0.96) than those in the bottom tertile. Greater adherence to the Carbo-vit pattern was inversely associated with the odds of low gait speed (OR: 0.46; 95% CI: 0.235-0.93). Conclusion: Major nutrient-based dietary patterns were significantly associated with sarcopenia and its components. Further studies are required to confirm our findings.